O-143 "You're never pregnant in the same way again": Prior early pregnancy loss influences needs for health care and support in subsequent pregnancy. (30th June 2022) - Koert, E; Nielsen, H.S; Schmidt, L
Abstract: Study question: What are couples' needs for health care and support in subsequent pregnancy after prior early pregnancy loss and do these needs change across the pregnancy? Summary answer: Couples described unmet needs for pregnancy care in the first 20 weeks of pregnancy and were satisfied with care provided the remainder of the pregnancy.  What is known already: Despite early pregnancy loss (PL) being common (∼25% of pregnancies), there is a paucity of research to guide practice to optimize treatment and support future pregnancies. There has been low priority in research and pervasive acceptance that couples should "just try again" after experiencing PL.  However, the notion that PL is a single event without wider implications has been challenged. Women with prior PL report increased anxiety during the first trimester of pregnancy compared to those without previous PL. No longitudinal studies explore whether anxiety persists across trimesters, how partners are impacted, and what couples' needs are throughout the pregnancy. Study design, size, duration: This was a qualitative longitudinal study. During first year of data collection, 13 couples who were pregnant after a prior pregnancy loss were interviewed four times over their pregnancy. Couples were recruited from the Copenhagen Pregnancy Loss Research Programme at Hvidovre Hospital, Denmark. Interviews were held in person at the hospital or university or online. Interviews ranged from 20 to 90 minutes (average= 52 min). Data collection is ongoing and full data will be presented. Participants/materials, setting, methods: Couples with at least one prior pregnancy loss who self-reported a new pregnancy and were willing to be interviewed together and in English were eligible to participate. Couples were interviewed together after a positive pregnancy test and once in each trimester. Interviews were transcribed and data was analyzed using thematic analysis to compare and contrast needs and experiences within and across the four time-periods. One same-sex couple and 12 heterosexual couples participated. Main results and the role of chance: Couples' needs were categorized into two themes: The first 20 weeks: high needs for pregnancy care with low/varied access: Couples wished for access to regular scans and close monitoring of the fetus to provide reassurance and detect problems early, but described considerable variation in the early pregnancy care offered, with many expressing unmet needs. Their need was more acute during the first 12 weeks, but persisted until the 20-week scan. Women described "surviving from scan to scan" with anxiety and fear about the safety of the fetus.  Some paid for private comfort scans if they did not have access. Both partners continued to process the grief and self-described "trauma" of the prior pregnancy loss and wished for psychological support during this period. The second 20 weeks: met needs for pregnancy care with high access: Couples expressed satisfaction with care including access to regular or extended antenatal support, access to 24 hour telephone support by midwife/nurse, and confirmation of good health at 20 week scan. They felt reassured there was some plan for their care. They felt more hopeful and shifted their focus to the current pregnancy and future birth, especially given increasing "signs of life" whilst the baby started to kick. Limitations, reasons for caution: Participants were self-selected thus findings cannot be generalized to all pregnant couples after early pregnancy loss. Single women were not included in the study. Wider implications of the findings: The findings underscore that an early pregnancy loss is not a single event without wider implications, but rather creates vulnerability and increased need for monitoring and care in a subsequent pregnancy, which in many cases is not met by existing early pregnancy care. Trial registration number: No